A Bibliometric Analysis and Visualisation of Research Trends in Allergy of Chromium Implants - Chauhan , Jasgurpreet Singh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The metal hypersensitivity of implants is a vital factor affecting the safety of implants. The bibliometric analysis had been conducted to understand the active authors, organizations, journals, and countries involved in the research domain of “allergy of Chromium implants”. All published articles related to “allergy of Chromium implants” from “Scopus”, were analyzed using the VOS viewer to develop analysis tables and visualization maps. This article had set the objective to consolidate the scientific literature regarding “allergy of Chromium implants” and also to find out the trends related to the same. The most active journal related to this research domain was Contact Dermatitis. The most active countries were the United States of America and Germany. The leading organization was Ludwig Maximilian University of Munich, Germany. The most active authors who had made valuable contributions related to the allergy of implants was Thomas P.